The Brand Scandal Spillover Effect at the Country Level: Evidence From Event-Related Potentials - Fan, Bonai; Li, Chen; Jin, Jia (Frontiers in Neuroscience, 2020)
The spillover effect of brand scandal commonly exists, which will damage the image of company, industry or even country. Most previous studies on brand scandal spillover effect have mainly focused on the corporate and industry levels. However, with the development of brand internalization and media technology, the spillover effect to the country level is becoming increasingly common. In the current study, we conducted an event-related potentials (ERPs) study to explore spillover effect of brand scandal on country level as well as its underlying neural basis. Specifically, we compared consumers’ attitude towards countries of origin with different stereotypes during different types of brand scandals. When a competence scandal happened, a competence stereotype country received a lower evaluation of country image than did a warmth stereotype country. When a competence scandal took place in a competence stereotype country, a larger P2 mean amplitude would be elicited compared to the warmth stereotype country. When a morality scandal took place in warmth stereotype country, a larger LPP mean amplitude would be induced compared to the competence stereotype country. We explain the current results based on expectancy violations theory. When competence scandals took place in competence stereotype countries, there will be a greater degree of violation of expectations compared with which took place in warmth stereotype countries. The violations of expectation lead to negative evaluation of the country of origin.